2015
DOI: 10.1371/journal.pone.0142153
|View full text |Cite
|
Sign up to set email alerts
|

p21WAF1 Is Required for Interleukin-16-Induced Migration and Invasion of Vascular Smooth Muscle Cells via the p38MAPK/Sp-1/MMP-9 Pathway

Abstract: Interleukin-16 (IL-16) is a lymphocyte chemoattractant factor well known for its role in immune responses, but its role in vascular disease is unknown. Here, we explored the novel physiological function of IL-16 in vascular smooth muscle cells (VSMCs). The expression of IL-16 and its receptor CD4 was observed in VSMCs. Treatment with IL-16 enhanced the migration and invasion by VSMCs without altering the proliferative potential. IL-16 induced MMP-9 expression via the binding activity of transcription factors N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 29 publications
0
18
0
1
Order By: Relevance
“…Stimulation of the P38 kinase cascade leads to HSP27 phosphorylation, then the phosphorylated HSP27 is released from the plus end of the actin filament, and these processes are important for actin reorganization and cell motility . In addition, the activation of P38 in response to chemical stressors induces cell invasiveness, which is reported to be associated with increased MMP9 secretion . In this study, several lines of evidence indicated that MICAL2 promoted breast cancer cell migration at least partially through EGFR/P38 signalling pathway.…”
Section: Discussionmentioning
confidence: 53%
“…Stimulation of the P38 kinase cascade leads to HSP27 phosphorylation, then the phosphorylated HSP27 is released from the plus end of the actin filament, and these processes are important for actin reorganization and cell motility . In addition, the activation of P38 in response to chemical stressors induces cell invasiveness, which is reported to be associated with increased MMP9 secretion . In this study, several lines of evidence indicated that MICAL2 promoted breast cancer cell migration at least partially through EGFR/P38 signalling pathway.…”
Section: Discussionmentioning
confidence: 53%
“…Regulation of MMP‐9 expression might be controlled through its transcription factors, particularly SP‐1, AP‐1, NF‐κB, and polyomavirus enhancer activator (PEA). For example, hydroquinone stimulates MMP‐9 expression through AP‐1, kindlin‐2 promotes MMP‐9 expression through NF‐κB in prostate cancer, the cell cycle inhibitor p21WAF‐1 regulates MMP‐9 expression through p38/SP‐1 pathway, and PEA‐3 is necessary for MMP‐9 regulation in ovarian cancer . Hence, we used the luciferase assay to examine MMP‐9 promoter activity; the results showed that melatonin suppresses MMP‐9 promoter activity through the SP‐1 region of HONE‐1 and NPC‐39 cells.…”
Section: Discussionmentioning
confidence: 99%
“…For blocking non‐specific antigen, the PVDF membrane was immersed in Tris‐buffered saline 0.2% Tween 20 (TBS‐T) and 5% skim milk at 4°C overnight. Then, the PVDF membrane was immersed in TBS‐T containing 5% skim milk and primary antibodies for detecting L5 receptor (LOX1), STRA6 signaling (STRA6, CRBP1, RARα and RXRα), phosphorylation of atherogenic p38MAPK (p‐p38MAPK and p38MAPK) and Smads pathway (pSmad2 and Smad2), and markers of atherogenesis (TGFβ 1 , caspase 3 and MMP9) in aortic cells. After washing with TBS‐T, the PVDF membrane was immersed in TBS‐T containing 5% skim milk and a 1:10,000 dilution of horseradish peroxidase‐conjugated antibody.…”
Section: Methodsmentioning
confidence: 99%